Off-pump Coronary Artery Bypass Grafting in Moyamoya Disease: a Case Report - Coşkun,Elif (2018)
Abstract Moyamoya disease is a rare, idiopathic, progressive, occlusive disease of the internal carotid artery characterized by the development of collateral vasculature in the brain base. In patients with accompanying coronary artery disease, cardiopulmonary bypass posses a potential risk for perioperative cerebral ischemic complication. Herein, we report a 53-year-old male case of Moyamoya disease and coronary artery disease who was treated with off-pump coronary artery bypass grafting.